1992
DOI: 10.1111/j.1600-0447.1992.tb01476.x
|View full text |Cite
|
Sign up to set email alerts
|

Early signs of cognitive deficits among human immunodeficiency virus‐positive hemophiliacs

Abstract: A total of 181 human immunodeficiency virus (HIV)-seropositive hemophiliacs and 28 hemophilic controls were evaluated by psychometric tests and by electroencephalogram (EEG). Patients were classified from stages 1-6 according to the immunological criteria of the Walter Reed staging system. Statistical analysis of psychometric data showed an effect of the stage of the disease on test performances, indicating a decline in attention, accumulation of perceptual interferences, decline in visuoperceptual speed and v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

1993
1993
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 30 publications
0
15
0
1
Order By: Relevance
“…The work of Riedel et al (1992) further demonstrated support for the subcortical profile of memory deficits reflected by spared recognition but decreased recall of verbal memory. In this study, no significant deficits were noted in visual memory.…”
Section: Introductionmentioning
confidence: 88%
“…The work of Riedel et al (1992) further demonstrated support for the subcortical profile of memory deficits reflected by spared recognition but decreased recall of verbal memory. In this study, no significant deficits were noted in visual memory.…”
Section: Introductionmentioning
confidence: 88%
“…This constellation of symptoms is a common feature of AIDS and has been referred to as AIDS related dementia. The existence of early cognitive and motor de®cits associated with the asymptomatic phase of HIV infection is now also clear, although these de®cits may be quite subtle (Borstein et al, 1992;Sinforiani et al, 1991;Clifford et al, 1990;McAllister et al, 1992;Perry et al, 1989;Riedel et al, 1992;Arendt et al, 1990;Martin et al, 1991Martin et al, , 1992aKarlsen et al, 1992a, b). Upon post mortem examination, estimates of the number of AIDS patients with CNS lesions range as high as 80% (Elder et al, 1988).…”
Section: Introductionmentioning
confidence: 99%
“…All such studies have divided HIV+ hemophiliacs into sub-groups according to patients’ immune functioning and the authors of such studies concluded that significant differences in several cognitive functions arise with the decrease of immunological functioning, and especially when the CD4+ cell counts ≤200. For example, Riedel et al (1992) identified a linear association between the scarce neuropsychological function in attention, motor skills, visual performance, and the decrease of CD4+. Similarly, according to Blanchette et al (2002), HIV+ hemophiliacs have shown impairments in motor speed and fine motor skills, in comparison with those shown by HIV− hemophiliacs.…”
Section: Resultsmentioning
confidence: 99%
“…Studies from different countries, including large cohorts as the HGDS, report a long-term decline in neurocognitive functions in around 15–50% of patients (Loveland et al, 1994; Sirois et al, 1998). Decline seems to be proportional with the decrease of immunological functioning, especially when the CD4+ cell counts ≤200 (Riedel et al, 1992; Nichols et al, 2000; Blanchette et al, 2002), even though other studies have concluded that the decline is related to hemophilia per se (Hilgartner et al, 1993; Whitt et al, 1993; Loveland et al, 1994; Sirois et al, 1998). …”
Section: Discussionmentioning
confidence: 99%